A Karyological Study of Tenualosa Ilisha (Hamilton, 1822) From the Confluence of Padma and Meghna River of Bangladesh (Bangladesh Journal of Zoology, 2021)
Tenualosa ilisha (Hamilton, 1822), commonly known as Hilsha shad is a valuable and highly acceptable species in terms of their high flavored properties. Hilsha shad has striking morpho-genetical adaptation to heterogeneous habitats across their migratory routes. Cytogenetic analysis demonstrates the changes in chromosomes. But none was focused on the cytogenetic analysis of T. ilisha in Bangladesh. T. ilisha was found to possess 2n = 42 number of chromosomes along with a karyotype formula: 1M + 31m + 8sm + 2st using giemsa staining technique. The results demonstrated ‘diffuse type of interphase nuclei, co-existence of continuous type and interstitial type of prophase chromosomes respectively. No heteromorphic sex chromosomes were determined cytologically. The presence of diverse types of chromosomes based on centromeric position, gradual decrease in total haploid chromosome complement, mean centromeric asymmetry, coefficient of variation of chromosome length and Stebbins’s classification highlighted its asymmetry in karyotype with advance nature. Therefore, the elemental karyological data will offer information for the proper identification, cytotaxonomical classification, expanding productivity and preservation of genetic resources ofT. ilisha.Bangladesh J. Zool. 49 (2): 243-255, 2021